Depression: an individual-level early warning indicator of virologic failure in HIV patients in South Africa - J.A. Edwards; J. Brijkumar; M. Dudgeon; C. Robichaux; B. Johnson; L. Rautman; R.A. Powers; Y.V. Sun; S. Pillay; C. Ordonez; J. Castillo-Mancilla; F.C. Tanser; et al. (The Union, 2024)
OBJECTIVE: To identify individual-level early warning indicators of virologic failure in HIV patients receiving antiretroviral therapy (ART) in South Africa. DESIGN: A matched case-control study of individuals with and without virologic failure (VF) (>5 months on ART and HIV-1 plasma viral load >1,000 copies/mL) was conducted between June 2014 and June 2018. Of the 1,000 participants enrolled in the parent cohort, 96 experienced VF, and 199 additional controls were identified from the parent cohort and matched 1:2 (some matched 1:3) for sex, age, ART duration, and site. Participants were interviewed while clinical, pharmacy refill, laboratory, and objective pharmacological data were obtained. Multivariate conditional logistic regression models were constructed using model selection to identify factors associated with VF. Significant determinants of VF were identified using an alpha level of 0.05. RESULTS: In a full conditional model, higher cumulative ART adherence, quantified using tenofovir-diphosphate concentrations in dried blood spots (OR 0.26) and medication possession ratio (OR 0.98) were protective against VF, whereas an increase in total depression score (OR 1.20) was predictive of VF. CONCLUSION: This analysis demonstrates the importance of depression as a key individual-level early warning indicator of VF. Efforts to address mental health concerns among patients with people living with HIV could improve virologic suppression.